2020
DOI: 10.4194/2459-1831-v4_2_02
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Proteomics for Identification of ReproductionRelated Proteins in Testes of the Giant Tiger Shrimp Penaeus monodon

Abstract: Testicular proteome of wild and domesticated 14- and 18-month-old broodstock of the giant tiger shrimp Penaeus monodon was examined. Among 344 differentially expressed proteins identified, 11 proteins (e.g. p97/VCP-binding protein p135, lipoxygenase homology domains 1 and dipeptidyl-peptidase, accounting for 4.95% of proteins with known functions) were found in wild broodstock but not in domesticated broodstock while 152 (68.47%) proteins were commonly found in all groups of samples. Reproduction-related prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The AX-249,988,993 (LG31, pos: 26.457 cM) and AX-249,687,820 (LG31, pos: 28.246 cM) SNPs intercepted the oplophorus-luciferin 2-monooxygenase and serine/arginine repetitive matrix protein genes, respectively. Although these genes are not directly related to sex determination, some studies shown that they are expressed in the gonads of crustaceans, such as Macrobrachium nipponense [ 33 ] and Penaeus monodon [ 34 , 35 ]. Another interesting gene, spermine oxidase , was found close to the AX-249,610,151 SNP (~ 20Kb downstream).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The AX-249,988,993 (LG31, pos: 26.457 cM) and AX-249,687,820 (LG31, pos: 28.246 cM) SNPs intercepted the oplophorus-luciferin 2-monooxygenase and serine/arginine repetitive matrix protein genes, respectively. Although these genes are not directly related to sex determination, some studies shown that they are expressed in the gonads of crustaceans, such as Macrobrachium nipponense [ 33 ] and Penaeus monodon [ 34 , 35 ]. Another interesting gene, spermine oxidase , was found close to the AX-249,610,151 SNP (~ 20Kb downstream).…”
Section: Resultsmentioning
confidence: 99%
“…The second gene was downregulated in the testis and ovary tissues of P. monodon using transcriptomic analysis [ 35 ]. Serine-arginine proteins have been reported to be differentially expressed during the testis maturation process of the same species [ 34 ]. The spermine oxidase gene is closely related to a significant SNP.…”
Section: Discussionmentioning
confidence: 99%
“…The second gene was found downregulated in testis and ovary tissues of P. monodon using transcriptomic analysis [36]. The serine-arginine protein was reported differentially expressed in the testis maturation process of the same species [35]. The spermine oxidase gene was found close to a signi cant SNP.…”
Section: Discussionmentioning
confidence: 99%
“…The AX-249988993 (LG31, pos:26.457 cM) and the AX-249687820 (LG31, pos: 28.246 cM) SNPs intercepted oplophorus-luciferin 2-monooxygenase and serine/arginine repetitive matrix protein genes, respectively. Although these genes are not directly related to sexual determination, some studies found them expressed in the gonads of crustaceans, such as Macrobrachium nipponense [34] and Penaeus monodon [35,36]. Another interesting gene called spermine oxidase was found close to the AX-249610151 SNP (~ 20Kb downstream).…”
Section: Genetic Linkage Mapmentioning
confidence: 99%
“…Proteomics is a powerful tool widely used to investigate protein expression and identify potential biomarkers or activated proteins [ 37 ]. This technique can be used to identify proteins regulated by post-translational modification that cannot be detected using genomic or transcriptomic methods [ 32 ]. The aim of the present study was to investigate the effects of cordycepin on protein expression in the brains of streptozotocin (STZ)-induced diabetic mice and clarify the mechanisms underlying its effects on diabetes-associated cognitive impairment.…”
mentioning
confidence: 99%